Scientists About Scientist: Reconstruction of the Image of Russian Scientist Based on Journal of Russian Academy of Science - S. M. Medvedeva (Vestnik MGIMO-Universiteta)
The article analyzes a stereotypical image of Russian scientist, published in a range of books of Russian Academy of Science. This image represents a construction of an ideal Russian scientist, who possesses the most desirable personal characteristics and reflects values of Russian scientific community. The article stresses, that popularization of such an image would contribute to rise of prestige of Russian science and profession of scientist.